2021
DOI: 10.3390/su131911090
|View full text |Cite
|
Sign up to set email alerts
|

Does the Vision 2030 and Value Added Tax Leads to Sustainable Economic Growth: The Case of Saudi Arabia?

Abstract: The motivation behind the current research is to check the effect of the recent introduction of value added tax (VAT) and Vision 2030 on the economy of Saudi Arabia. To check this, those variables are added to the analysis which contribute to economic development including labor, capital, oil price, financial development, and trade openness to examine that how economic transformation affects the role of these variables in economic growth. According to the vector error correction (VEC) model, the impact of labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…As all variables are stationary at a level, exploring the cointegration between variables is necessary. Pedroni cointegration is used in this study to check the long-run association between variables, as followed by Sarwar et al ( 48 ) and Waheed et al ( 49 ), and results are reported in Table 6 . It can be noted that six out of seven statistics are significant at a 1% level of significance.…”
Section: Resultsmentioning
confidence: 99%
“…As all variables are stationary at a level, exploring the cointegration between variables is necessary. Pedroni cointegration is used in this study to check the long-run association between variables, as followed by Sarwar et al ( 48 ) and Waheed et al ( 49 ), and results are reported in Table 6 . It can be noted that six out of seven statistics are significant at a 1% level of significance.…”
Section: Resultsmentioning
confidence: 99%
“…Using a VEC model, this study examines the impact of the recent VAT implementation and Vision 2030 on the Saudi economy. Different coefficient results are observed for restructuring the export/import policies: financial growth, oil prices, and trade openness are bad, while trade openness is positive (Sarwar et al, 2021).…”
Section: Other Variables Co 2 Emissions and Economic Growthmentioning
confidence: 89%
“…Using a VEC model, this study examines the impact of the recent VAT implementation and Vision 2030 on the Saudi economy. Different coefficient results are observed for restructuring the export/import policies: financial growth, oil prices, and trade openness are bad, while trade openness is positive (Sarwar et al, 2021). Using “Partial least squares structural equation modeling” (PLS‐SEM), this study aims to determine the main obstacles that 79 users of biogas plants face when deploying their plants.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Through negative and positive partial sum decompositions of independent variates, the NARDL model combines long-run and short run nonlinearities. The partial sum approach is used in asymmetric decomposition to integrate the decrease and increase in the variables Khalfaoui et al (2021) ; Sarwar et al (2021) ; Sarwar et al (2021) . Furthermore, Hatemi-J (2012) causality test is used to determine the asymmetric causality direction.…”
Section: Empirical Methodologymentioning
confidence: 99%